Analysis of the Influence of the Gas Infrared Heater and Equipment Element Relative Positions on Industrial Premises Thermal Conditions; Energies; Vol. 15, iss. 22 - Borisov B. V. Boris Vladimirovich; Vyatkin A. V. Aleksandr Vitaljevich; Kuznetsov G. V. Geny Vladimirovich; Maksimov V. I. Vyacheslav Ivanovich; Nagornova T. A. Tatiana Aleksandrovna (2022, 2022)
Title screen